COMPARISON AND MOLECULAR PROFILING OF BEGOMOVIRUS INFECTING CHILLI (Capsicum annum) IN GANGETIC ALLUVIAL ZONE OF WEST BENGAL - UDAY BIKASH ORAON,; LOUREMBAM SANAJAOBA SINGH,; JAYANTA TARAFDAR, (The Bioscan, 2020)
In our present investigation the leaf curl disease on chilli was observed up to an extent of 18-85% at different regions Gangetic alluvial zone of West Bengal. Symptoms like upward leaf-curling, distortion, vein yellowing, leaf yellowing and/or stunted growth with bushy appearance of chilli plants observed in the fields. The disease was successfully transmitted by whitefly (Bemisia tabaci), on experimental plants. The total DNA was extracted from infected leaf samples and PCR was carried out using a pair of begomovirus-specific degenerate primers (SPG1/SPG2). The replication-associated protein gene fragment (Rep; AC1) of 920 bp were amplified from naturally begomovirus-infected and experimentally vector transmitted plants. After sequencing, Phylogenetic analysis of partial nucleotide sequences of DNA-A revealed that Bongaon-24parganas-WB begomovirus isolate (Accession no. LT622253) made separate cluster and showed 91% nucleotide sequence identity with Pepper leaf curl Bangladesh virus (Accession no. AF314531) and Dhatrigram-Burdwan-WB begomovirus isolate (Accession no. LT622254) is clustered with Pepper leaf curl Bangladesh virus India (Accession no. HM007111) with 95% nucleotide sequence identity.Moreover, these studies supply precise information about the frequency and distribution of distinct begomovirus isolates in chilli in Gangetic alluvial West Bengal.